Finding a hamilton path through a family of intervals - Sridhar, M. A.; Goyal, S. (International journal of computer mathematics, 1994)
We develop an o(nx(n)) algorithm for computing a hamilton path in a family of n intervals, where x is an inverse of Ackerman's function. Our approach is based on a new characterization of interval graphs containing hamilton paths, related to the clique decomposition of the graph.